Evaluation of the risk/benefit associated to the consumption of raw and cooked farmed meagre based on the bioaccessibility of selenium, eicosapentaenoic acid and docosahexaenoic acid, total mercury, and methylmercury determined by an in vitro digestion model. (1st March 2015) - Afonso, C.; Costa, S.; Cardoso, C.; Bandarra, N.M.; Batista, I.; Coelho, I.; Castanheira, I.; Nunes, M.L.
Highlights: Lipid bioaccessibility was high in raw and cooked meagre except grilled fish. EPA and DHA bioaccessibility was low in raw and cooked meagre. Se bioaccessibility was equal or higher than 82% (grilling treatment). Hg and MeHg bioaccessibility was high with exception of grilled meagre. Maxima 2 meals/week for boiled/roasted & 3 meals/week for grilled meagre are advised. Abstract: The bioaccessibility of total lipids, EPA, DHA, Se, Hg, and MeHg in raw and cooked meagre ( Argyrosomus regius ) was studied by using an in vitro digestion method. A risk–benefit assessment of raw and cooked meagre on the basis of the bioaccessibility data was carried out. The bioaccessibility of total lipids was generally high in raw and cooked meagre with exception of grilled fish. For EPA and DHA, bioaccessibility percentages were low never surpassing the 50% in raw, boiled, and grilled meagre. The bioaccessibility percentage of Se was equal or higher than 82% (grilling treatment). Likewise, for Hg and MeHg, high bioaccessibility values were determined with exception of grilled meagre, displaying lower values of 54% and 64%, respectively. The risk–benefit probabilistic assessment brought about a recommendation of a maximum consumption of two weekly meals for boiled or roasted meagre and three weekly meals for grilled meagre.